Revelation of the Technological Versatility of the Eu(TTA)3Phen Complex by Demonstrating Energy Harvesting, Ultraviolet Light Detection, Temperature Sensing, and Laser Applications - Shahi P.K.; Singh A.K.; Singh S.K.; Rai S.B.; Ullrich B. (My University, 2025)
We synthesized the Eu(TTA)3Phen complex and present herein a detailed study of its photophysics. The investigations encompass samples dispersed in poly(vinyl alcohol) and in ethanol in order to explore the versatile applicability of these lanthanide-based materials. Details upon the interaction between Eu, TTA, and the Phen ligands are revealed by Fourier transform infrared and UV-visible absorption, complemented by steady state and temporally resolved emission studies, which provide evidence of an efficient energy transfer from the organic ligands to the central Eu3+ ion. The material produces efficient emission even under sunlight exposure, a feature pointing toward suitability for luminescent solar concentrators and UV light sensing, which is demonstrated for intensities as low as 200 nW/cm2. The paper further promotes the complex's capability to be used as luminescence-based temperature sensor demonstrated by the considerable emission intensity changes of ∼4.0% per K in the temperature range of 50-305 K and ∼7% per K in the temeperature range 305-340 K. Finally, increasing the optical excitation causes both spontaneous emission amplification and emission peak narrowing in the Eu(TTA)3Phen complex dispersed in poly(vinyl alcohol) - features indicative of stimulated emission. These findings in conjunction with the fairly large stimulated emission cross-section of 4.29 × 10-20 cm2 demonstrate that the Eu(TTA)3Phen complex dispersed in poly(vinyl alcohol) could be a very promising material choice for lanthanide-polymer based laser architectures. (Graph Presented). © 2015 American Chemical Society.